2022
DOI: 10.1515/chem-2022-0127
|View full text |Cite
|
Sign up to set email alerts
|

A detailed investigation on highly dense CuZr bulk metallic glasses for shielding purposes

Abstract: Gamma-ray shielding properties of eight different metallic glasses based on CuxZr100-x: x = 35 (Cu35Zr65) − 70 (Cu70Zr30) were determined using Monte Carlo simulations and Phy-X/PSD software. A typical gamma-ray transmission setup has been modeled in MCNPX Monte Carlo code. The general trend of the linear attenuation coefficients (μ) was reported as (μ)Cu35Zr65 < (μ)Cu40Zr60 < (μ)Cu45Zr55 < (μ)Cu50Zr50 < (μ)Cu55Zr45 < (μ)Cu60Zr40 < (μ)Cu65Zr35 < (μ)Cu70Zr30. In terms of half value layer (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…The mass attenuation coefficient (μ m , cm 2 /g) is the main and fundamental shielding parameter which gives the interaction probability of photons with mass per unit area of the material. The linear attenuation coefficient (μ, cm −1 ) is equivalent to μ m , but it gives the fraction of attenuated radiation per unit thickness of the material [7,32,42,43]. The μ m and μ are calculated using a very familiar Beer-Lambert law, I = I 0 e − μ t .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mass attenuation coefficient (μ m , cm 2 /g) is the main and fundamental shielding parameter which gives the interaction probability of photons with mass per unit area of the material. The linear attenuation coefficient (μ, cm −1 ) is equivalent to μ m , but it gives the fraction of attenuated radiation per unit thickness of the material [7,32,42,43]. The μ m and μ are calculated using a very familiar Beer-Lambert law, I = I 0 e − μ t .…”
Section: Methodsmentioning
confidence: 99%
“…The mean free path (λ) is the average distance traveled by a photon before just a collision. The HVL, TVL, and λ are calculated using the relations, ln 2 1 ( )m -, ln 10 1 ( )m -, and μ −1 , respectively, and measured in cm unit [32,44]. The effective atomic number (Z eff ) of a composite material like BMG can not be expressed as a single number like elements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of the calculations, they suggested that metallic glasses Ti32.8Zr30.2Ni5.3Cu9Be22.7 and Ti31.9Zr33.4Fe4Cu8.7Be22 could be good radiation shielding materials. Tekin et al [16] investigated the radiation shielding capacities of metallic glasses having eight different concentrations in CuxZr100-x (x=35 (Cu35Zr65)-70(Cu70Zr30)) combination using MCNPX simulation and Phy-X/PSD interface. For this purpose, they calculated the linear and mass attenuation coefficients, half value layer, tenth value layer, mean free path, effective atomic number and electron density parameters in the energy range of 0.015 to 15 MeV.…”
Section: Introductionmentioning
confidence: 99%